A world without summer : a volcano erupts, a creature awakens, and the sun goes out - Day, Nicholas, 1991- (Random House Studio, 2025)
"A narrative nonfiction account that explores how Mount Tambora's eruption in 1815 affected the global climate and inspired Mary Shelley's work"-- Provided by publisher.